2011
DOI: 10.1111/j.1467-8535.2011.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Using video to analyze one's own teaching

Abstract: Recently, interest in using video to facilitate teacher reflection has increased. Despite this increase, the frameworks employed to help teachers use video to reflect on their teaching are not based on the results of prior video analysis research.There is a need to better understand how and in what ways video has been used to reflect on one's own teaching. The purpose of this paper is to review past studies in order to help educators make more informed decisions as they establish their own video analysis proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(121 citation statements)
references
References 35 publications
(44 reference statements)
2
107
1
11
Order By: Relevance
“…This type of questioning about the actionable behaviours on the list might support professional dialogue and reflection. Moreover, actionable behaviours might also be observed by others or self-observed through video reflection (see Cherrington, 2012;Tripp & Rich, 2012). Thus, the practice list can act as a tool to support teachers to identify areas of practice for professional reflection, learning, and research to strengthen their own capacity and confidence.…”
Section: Methodsmentioning
confidence: 99%
“…This type of questioning about the actionable behaviours on the list might support professional dialogue and reflection. Moreover, actionable behaviours might also be observed by others or self-observed through video reflection (see Cherrington, 2012;Tripp & Rich, 2012). Thus, the practice list can act as a tool to support teachers to identify areas of practice for professional reflection, learning, and research to strengthen their own capacity and confidence.…”
Section: Methodsmentioning
confidence: 99%
“…The instructional value of video-supported feedback is particularly emphasized in areas such as medicine and sport (e.g., Farquharson et al 2013;O'Donoghue 2006); that is, areas where skills and competence are visibly accessible through recordings of embodied actions. Video is also frequently used to support discussions about communication and professional conduct in the training of psychotherapists (Haggerty and Hilsenroth 2011), teachers (Tripp and Rich 2012;van Es 2009), and doctors (Beckman and Frankel 1994;Kurtz et al 2005). By watching themselves on video, it is argued, Bprofessionals are able to improve their receptive, informative and relational skills^ (Fukkink et al 2011, p. 56).…”
Section: Using Video For Self-reflection and Learningmentioning
confidence: 99%
“…Girod et al (2007) draw parallels between the phases in video production and the classroom teaching process, so as to emphasise the ways in which video-making enables teachers to reflect on their own practice. A study by Tripp and Rich (2012a) found that some teachers would only recognise the need to improve their teaching practice after watching and reflecting on videos of themselves in action (see also Tripp and Rich (2012b) for an extended review of literature that describes how the process of reflection is facilitated by video analysis). Studies have also shown that using video in teacher education supports the development of empathy and a sense of professional identity (Koc 2011).…”
Section: The Use Of Learner-generated Video In Higher Educationmentioning
confidence: 99%